Pikiran Damai Berdasarkan Penuturan Markesot: Studi Hermeneutika Teks Markesot Bertutur Lagi - Saputra, Wahyu; Supriyanto, Agus; Astuti, Budi; Ayriza, Yulia (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study aims to interpret peace based on a text entitled Markesot Bertutur Lagi by Emha Ainun Najib. This study used a qualitative approach with hermeneutics procedure. Each interpretation was an attempt to understand the meanings that are still veiled in a text. The data collection techniques in this study were carried out through the documentation of the interpretation of texts and literature studies. The interpretation was carried out in three stages: (1) whole understanding; (2) partial understanding; and (3) understanding of underlying meaning. The data analysis techniques in this study used the formulation of Miles & Huberman which included data reduction, data presentation, and inference. The results showed that the peaceful mind based on Markesot Bertutur Lagi was: (1) thinking to forgive the mistakes of others; (2) thinking of finding strength rather than blaming yourself; (3) thinking to regulate self-emotions; and (4) thinking to regulate self-behavior. These four forms of peace of mind should be a reference for the school counselor to be the basis for implementing peace counseling to build peaceful thoughts in students.